How can learners explain phenomena in ecology using evolutionary evidence from informal learning environments as resources? - Nesimyan – Agadi, Dina; Ben Zvi Assaraf, Orit (Journal of Biological Education, 2021)
The theory of evolution can be a useful basis for developing students’ understanding of ecology. Our study used concept maps to examine the development of sixth-grade students’ understanding of the Antarctic ecosystem following several evolution ‘Science Days’ conducted at ‘Nature Campus’ – an informal learning environment comprised of a natural history museum, zoological and botanical gardens. The programme included physical experiences, such as observations and measurements of fossils, skeletons and mounted specimens, and observations in the zoological and botanical gardens. After the first and fourth days, the students watched the film ‘March of the Penguins,’ and were asked to draw concept maps depicting the penguins’ lives. These maps were then analysed to assess: (a) the changes in the students’ depictions of the ecosystem’s complexity, and (b) the manner and extent to which they used ideas and concepts in evolution to explain phenomena in the Antarctic ecosystem. We found that the students’ concept maps increased in complexity, and their post-maps incorporated concepts in evolution from their experiences at Nature Campus. Our results therefore emphasise the benefits of fundamentally changing how biology education is divided and defined, and transitioning to a more holistic approach that acknowledges the interdisciplinary nature of biological phenomena.
Publisher: Routledge _eprint: https://doi.org/10.1080/00219266.2021.1877784
Keywords: Informal learning environment; concept maps; ecology; evolution; system thinking